Mestizo democracy : the politics of crossing borders - Burke, John Francis, 1957- (Texas A & M University Press, 2002)
Annotation It can come as no surprise that the ethnic makeup of the American population is rapidly changing. In this volume, John Francis Burke offers a "mestizo" theory of democracy and traces its implications for public policy. Mestizo, meaning "mixture, " is a term from the Mexican socio-political experience. It represents a blend of indigenous, African, and Spanish genes and cultures in Latin America. This mixture is not a "melting pot" experience; rather, the influences of the different cultures remain identifiable but influence each other in dynamic ways. Burke analyzes democratic theory and multiculturalism to develop a model for cultivating a community that can deal effectively with its cultural diversity. He applies this model to official language(s), voting and participation, equal employment opportunity, housing, and free trade. Burke concludes that in the United States we are becoming mestizo whether we know it or not and whether we like it or not. By embracing this, we can forge a future together that will be greater than the sum of its parts
Keywords: Multiculturalism -- United States.; Democracy -- United States.; Americanization.; Political culture -- United States.; United States -- Emigration and immigration.; Multiculturalisme -- États-Unis.; Américanisation.; États-Unis -- Émigration et immigration.; SOCIAL SCIENCE -- Anthropology -- Cultural.; SOCIAL SCIENCE -- Discrimination & Race Relations.; SOCIAL SCIENCE -- Minority Studies.; Americanization; Democracy; Emigration and immigration; Multiculturalism; Political culture; United States; Multikulturelle Gesellschaft; Demokratie; Politik; USA; Culture politique -- États-Unis.; Multiculturalismo -- Estados Unidos.; Democracia -- Estados Unidos.; Americanización.; Cultura política -- Estados Unidos.